Cellulose micro/nanocrystals reinforced polyurethane - Marcovich, Norma Esther (2006)
Nano- and micron-sized cellulose crystals were prepared and utilized as reinforcements for polyurethane composites. The cellulose crystals obtained from microcrystalline cellulose (MCC) were incorporated into a polar organic solvent, dimethylformamide (DMF), and ultrasonicated to obtain a stable suspension. The suspension was an effective means for incorporating the cellulose crystals into the polyol-isocyanate mixture, utilized to produce polyurethane composite films. The use of DMF presents an interesting alternative for the use of cellulose crystals as reinforcement of a broad new range of polymers. Moreover, the rheology of the uncured liquid suspensions was investigated, and analysis of the results indicated the formation of a filler structure pervading the liquid suspension. Besides, films were prepared by casting and thermal curing of the stable suspensions. Thermomechanical and mechanical testing of the films were carried out to analyze the performance of the composites. The results indicated that a strong filler-matrix interaction was developed during curing as a result of a chemical reaction occurring between the crystals and the isocyanate component.